Knowledge Retention Strategy for Dealing with Knowledge Loss at Bank Bisnis Headquarters - Kiki, Kiki; Hidajat Tjakraatmadja, Jann (The Indonesian Journal of Business Administration, 2016)
Abstract. One of major challenges for organizations nowadays is the aging and shortening of experienced workforces. As experienced or senior staff retire, then critical knowledge and their experience will leaving the company and will be a threat to company unless that knowledge can be successfully retained and transferred to other existing workers which less experienced. Due to high turnover, the retention of valuable organizational knowledge from senior and experienced workers has been recognized as an urgent need. Due to high employee turnover rate in the last two years at Bank XYZ Headquarters, will increase the possibility of critical knowledge leaves the company. In 2015, headquarters recorded the turnover rate was 24.39%, increase almost 3 times from the previous year, and most of them are experienced and senior staff. The goal of this research is to deal with knowledge loss at Bank XYZ by formulating Knowledge Retention Strategy by using the suitable Knowledge Retention framework. By using the Analytic Hierarchy Process (AHP) of Prof. Thomas L. Saaty (2001), acquired knowledge retention framework suitable for this study, which is selected from three alternative models of knowledge retention. With the selected framework of knowledge retention from Deller and Burmeister, this research finding out first what critical knowledge that posses by employee in Bank XYZ Headquarters and how to retain them.4 factors which help to formulate the strategy are critical knowledge, individual characteristic, relationship characteristic, and contextual characteristic. Based on the result of this analysis, the company have so many critical knowledge that need to be retain. This caused by lack of monitoring about knowledge retention and too formal interaction among employees that less support the retention activities.The result of this research is Bank XYZ Headquarters will implement Knowledge Retention Strategy to prevent knowledge loss in the future. The implementation run through 3 kind of activities: skill development and training, informal activities, and exit management. Based on knowledge retention framework analysis, all the retention activities will exactly as needed by Bank XYZ Headquarters employee.